2013
DOI: 10.1111/jcom.12063
|View full text |Cite
|
Sign up to set email alerts
|

Helpful or Harmful? How Frequent Repetition Affects Perceived Statement Credibility

Abstract: On the basis of experimental data, we study how repetition of a statement affects perceived statement credibility. We identify 2 counteracting effects: The first effect, known as “truth effect,” describes a positive relationship between repetition and statement credibility. People tend to ascribe higher credibility to messages that they repeatedly encounter. In contrast, the second effect occurs when repetition is taken too far. Here, an indirect and negative effect is identified and participants start to perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(73 citation statements)
references
References 84 publications
(140 reference statements)
7
64
1
1
Order By: Relevance
“…Instead, future studies should account for exposure time, too. These studies should also look for a possible suppression effect (Koch and Zerback 2013). Specifically, repeated celebrity endorsements may lead to enhanced advertising outcomes while at the same increasing the likelihood of evoking reactance due to too much (forced) exposure.…”
Section: Discussion Main Findings and Contributionsmentioning
confidence: 99%
“…Instead, future studies should account for exposure time, too. These studies should also look for a possible suppression effect (Koch and Zerback 2013). Specifically, repeated celebrity endorsements may lead to enhanced advertising outcomes while at the same increasing the likelihood of evoking reactance due to too much (forced) exposure.…”
Section: Discussion Main Findings and Contributionsmentioning
confidence: 99%
“…According to Brehm and Brehm (1981), "boomerang effects," like the self-promoter's paradox or the catch 22 in the case of CSR communication, "represent the best evidence for reactance theory" (Brehm & Brehm, 1981, p. 38). Individuals that receive persuasive messages preserve their personal freedoms by derogating the communicator's credibility (consistent with Koch & Zerback, 2013a, 2013bMeirick & Nisbett, 2011;Pomering & Johnson, 2009, p. 425). We therefore assume that H6.…”
Section: Indirect Negative Effectsmentioning
confidence: 63%
“…Reactance is a psychological reaction to everything that threatens personal freedoms, including persuasive communication (Brehm & Brehm, 1981, pp. 121-150;Koch & Zerback, 2013a, 2013bMeirick & Nisbett, 2011;Moyer-Gusé, Jain, & Chung, 2010;Quick et al, 2013). In line with reactance theory, we expect that H5.…”
Section: Indirect Negative Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Persuasion studies have found that repetitions will eventually lead to reactance and a decrease in message agreement (e.g. Koch & Zerback, 2013). This reactance could occur after as much as three repetitions (Cacioppo & Petty, 1979).…”
Section: Discussionmentioning
confidence: 94%